Method and Mechanism of Dump Overlying the Bedrock with Large Dip Angle in Opencast Mine - Hongze Zhao; Hairui Du; Zhigang Tao; Zechen Lin (Advances in Civil Engineering)
Dump in the steep area of the open-pit mine is essential for safe production. The bedrock with the bumpy-surface blasting method effectively improves the stabilization of the dumpsite. The effect of the ratio and dispersion degree on the deformation and failure of the dumping bench at the largely inclined area was analyzed. Based on the limit equilibrium method, the equation about the stability factor and the blasted region ratio was deduced. Virtual experiments were performed to address how the ratio and dispersion degree affect deformation and failure. The results showed that the stability factor is a quadratic function of the ratio of the blasted area. The increase in the ratio results in a drastic reduction of displacement, and the direction of displacement significantly changes. The rise in the dispersion degree effectively reduces the displacement and shear strain increment, and the failure mode changes. There is a specific value for the ratio and dispersion degree, making the displacement and shear strain increment little. The research on bumpy surface blasting in this paper provides the theoretical foundation for the dump construction at the site with the large dip angle.